Effectiveness and active ingredients of social prescribing interventions targeting mental health: a systematic review - Darren Flynn; Jason Scott; Matthew Cooper; Leah Avery; Linda Errington; Kirsten Ashley; Cara Jordan (BMJ Open)
Objective This study aims to establish the effectiveness and active ingredients of UK-based social prescribing interventions targeting mental health and well-being outcomes.Design Systematic review adhering to Preferred Reporting Items for Systematic Reviews and Meta-Analysies guidelines and a published protocol.Data sources Nine databases were systematically searched up to March 2022.Eligibility criteria Social prescribing interventions in the UK involving adults aged ≥18 years, which reported on mental health outcomes.Data extraction and synthesis Two reviewers extracted data on study characteristics; outcomes; referral pathways; treatment fidelity strategies; person-centredness; intervention development processes and theory-linked behaviour change techniques (BCTs). Data were narratively synthesised.Results 52 074 records were retrieved by the search, 13 interventions reported across 17 studies were included in this review (N=5036 participants at post-intervention). Fifteen studies were uncontrolled before-and-after designs, one a randomised controlled trial and one a matched groups design. The most frequently reported referral pathway was the link worker model (n=12), followed by direct referrals from community services (n=3). Participants were predominantly working age adults, and were referred for anxiety, depression, social isolation and loneliness. 16 out of 17 studies reported statistically significant improvements in outcomes (mental health, mental well-being, general health, or quality of life). Strategies to enhance treatment fidelity were suboptimal across studies. Only two studies used a specific theoretical framework. A few studies reported engaging service users in codesign (n=2) or usability and/or feasibility testing (n=4). Overall, 22 BCTs were coded across 13 interventions. The most frequently coded BCTs were social support-unspecified (n=11), credible source (n=7) and social support-practical (n=6).Conclusions Robust conclusions on the effectiveness of social prescribing for mental health-related outcomes cannot be made. Future research would benefit from comprehensive intervention developmental processes, with reference to appropriate theory, alongside long-term follow-up outcome assessment, using treatment fidelity strategies and a focus on principle of person-centred care.PROSPERO registration number CRD42020167887.